The Socialization Process of Work Placement Students (An exploratory study) - Aldaya, Kathrin (2008)
This paper examines the socialization experience of temporary work placement students within their companies. A major reason behind this dissertation is that no previous research has so far been dedicated to the topic and tried to explore how the socialization of temporary employees differs from that of permanent ones and how employers could improve the experience which their internship students go through.